Analisis Pertumbuhan Platform Bisnis Digital di Indonesia - Isrania; Meilin Meilin; Natalie Emantonio; Rani Sofia Magdalena; Angela Wulandari (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the growth of digital business platforms in Indonesia, the factors influencing their growth, and their impact on the economy and society. The research employs a qualitative method with a literature review approach. Data were collected from various secondary sources, including scientific journals, official reports, and government policy documents. The findings indicate that the growth of digital business platforms in Indonesia is driven by several key factors, such as massive internet penetration, changes in consumer behavior, technological innovation, aggressive marketing strategies, government policy support, and extensive geographical reach. The positive impacts of this growth include increased market access for MSMEs, the creation of new job opportunities, and enhanced economic efficiency. However, challenges such as the digital divide, data security concerns, and disruptions to traditional businesses remain. This study provides recommendations for the government and business actors to address these challenges and maximize the potential of digital economic growth in Indonesia.